Association between Ventilation Disorder and Masticatory Dysfunction in the Korean Adult Population: A Cross-Sectional Study Using Data from the 2019 Korea National Health and Nutrition Examination Survey - So-Yeong Kim; Sun-A Lim (Medicina)
Background and Objectives: Respiratory and periodontal diseases are among the most common diseases affecting humans worldwide. Periodontal disease is a risk factor for aspiration pneumonia and other respiratory diseases. However, the evidence supporting the link between respiratory and periodontal disease is inconclusive and insufficient. Therefore, this study aimed to investigate the relationship between oral disease symptoms and respiratory diseases. Materials and Methods: Adults who underwent oral examinations and lung disease tests were recruited from the 2019 Korea National Health and Nutrition Examination Survey (KNHANES). A total of 14,956 individuals participated in the 2019 KNHANES. Among the 6846 participants who underwent oral examinations, 1320 children and adolescents were excluded. Additionally, of the 4119 adults aged ≥40 years who underwent dual lung function tests, those who did not respond to key independent confounding variables were excluded. The final sample consisted of 2988 adults. Results: Complex sample multivariate logistic regression analysis revealed that the risk of restrictive ventilation disorder was lower in individuals without chewing discomfort compared to individuals with chewing discomfort (odds ratio, 0.68; 95% confidence interval, 0.479–0.996), and the difference was statistically significant. Only one significant difference was observed between the two groups. Conclusions: Chewing discomfort is a major periodontal health-related factor associated with chronic obstructive pulmonary disease (COPD). Although the exact mechanism underlying the relationship between masticatory discomfort and COPD remains unclear, masticatory discomfort is an early symptom of oral diseases. The findings from this study provide additional basic data for the prevention of oral diseases and COPD in Korea.